Transcatheter Edge-To-Edge Repair of A Tricuspid Valve Regurgitation In A Patient with Previous Prosthetic Annuloplasty Ring and DDD Pacemaker - Goette, Andreas; Hasmasan, Mihai; Brandner, Sibylle (Archives of Clinical and Medical Case Reports, 2024)
Background: Residual tricuspid regurgitation (TR) may occur in up to 30% of patients after surgical tricuspid annuloplasty. It is unclear at present if transcatheter edge-to-edge repair (TEER) is feasible in these patients. Case Summary: The patient was a 71-year-old woman with a history of severe mitral and tricuspid regurgitation. 8 years prior, she had undergone bioprosthetic mitral valve replacement and tricuspid valve prosthetic ring annuloplasty. A DDD pacemaker had been implanted due to complete AV block after AV-node-ablation. The patient complained of worsening right heart failure symptoms, with severe peripheral edema and shortness of breath. Echocardiography demonstrated normal left ventricular function. The implanted mitral valve did show only a mild regurgitation. But a massive tricuspid regurgitation Grad V was documented (vena contractae width of 11 mm). Due to lack of other treatment options TEER was performed by using the TriClip® device (Abbott, Vascular GmbH). During the TEER procedure, it was difficult to visualize the tricuspid leaflets in transesophageal echocardiography (TEE) due to shadowing from the prosthetic annuloplasty ring. This was resolved by utilizing transgastric visualisation of the tricuspid valve. The right ventricular lead was visualized by X ray and echocardiography during the procedure. The TEER device was implanted posterior to the RV lead, which resulted in a reduction of TR (Grad II). Pacemaker interrogation did not show alteration of RV sensing or pacing. Discussion: TEER is feasible in severe TR following a prosthetic annuloplasty ring procedure of the tricuspid valve even in the presence of right ventricular pacemaker lead. Thus, TEER appears as a treatment option for patients with a failed prosthetic annuloplasty repair/with recurrent massive TR after prosthetic annuloplasty.